Moderation in the Quran and Sunnah and the views of the contemporary scholars | الوسطية في الكتاب والسنة وأراء المعاصرين فيها - Iffatul Umniati Ismail (Al-Zahra : Journal for Islamic and Arabic Studies, 2010)
The topic of the Research is about the concept of moderation according to theQuran and hadith. TI1e inoderation - al-washathiyah- in Islam means excellence(khiyar), justice (al- 'ad0, goodness (thayyibah) and truth (al-haqq). The feature ofthis research is how it describes about the concept of al Quran and sunnah inmoderation, and also mentioned the thought of some classic and contemporarymuslirn scholars such as Imam Shafii, Shaikh al-Ghazali, Muhammad Imarah,Yusuf al-Qaradl1awi. This reseaTch refers to the Qur'an, Sunnal1, and bothclassic and modem books.